Now or never: perceptions of uniqueness induce acceptance of price increases for experiences more than for objects - Bastos, Wilson (2021)
Seven studies test and support the prediction that consumers are more willing to accept a price increase for an experiential versus a material purchase; an effect explained by the greater uniqueness of experiences. Critically, the uniqueness model advanced here is found to be independent of the happiness consumers derive from the purchase. To gain a deeper understanding of the uniqueness mechanism, this investigation then advances and tests a four-facet framework of uniqueness (unique opportunity, unique purchase, unique identity, and counterconformity). Together, the findings converge on the conclusion that consumers perceive the opportunity to have a particular experience (vs. object) as more unique, and this unique opportunity increases their willingness to accept a price increase. Overall, this work extends the experiential versus material purchases literature into a new domain—that of pricing; identifies the dimension—uniqueness—and its precise facet responsible for the effect—unique opportunity; and demonstrates that this model unfolds in a pattern distinct from the oft researched model centered on consumer happiness. Theoretical and practical implications are discussed.